2011
DOI: 10.1038/labinvest.2011.9
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine abolishes MTX-induced suppression of osteoclastogenesis and inflammatory bone destruction in adjuvant-induced arthritis

Abstract: Methotrexate (MTX) is widely utilized for the treatment of patients with rheumatoid arthritis (RA); however, recent observation of the MTX-resistant patients proposed some difficulty in MTX-dependent therapeutic approach for RA. To access cellular events related to MTX resistance in RA in respect to inflammatory bone destruction, we investigated on an involvement of the potent inflammatory mediator adenosine in the regulation of osteoclastogenesis and inflammatory bone destruction. In rats with adjuvant-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 38 publications
(39 reference statements)
2
13
1
Order By: Relevance
“…Moreover, we have observed dose-dependent inhibition of RANKL-induced osteoclast formation and expression of osteoclast markers by the A 2b R specific agonist BAY 60-6,583 in murine BMMs (supplemental Figure 1). These observations contrast, at least at a superficial level, with those of Teramachi et al [49] who reported that adenosine abolished MTX-induced osteoclast inhibition via stimulation of A 2b receptors. However, the effects described by Teramachi and colleagues are most likely mediated by A 2b receptors on osteoblasts since, as noted in their work, the primary reason for inhibition of osteoclast formation in these bone marrow cultures was inhibition of RANKL expression without diminution of osteoprotegerin expression.…”
Section: Discussioncontrasting
confidence: 83%
“…Moreover, we have observed dose-dependent inhibition of RANKL-induced osteoclast formation and expression of osteoclast markers by the A 2b R specific agonist BAY 60-6,583 in murine BMMs (supplemental Figure 1). These observations contrast, at least at a superficial level, with those of Teramachi et al [49] who reported that adenosine abolished MTX-induced osteoclast inhibition via stimulation of A 2b receptors. However, the effects described by Teramachi and colleagues are most likely mediated by A 2b receptors on osteoblasts since, as noted in their work, the primary reason for inhibition of osteoclast formation in these bone marrow cultures was inhibition of RANKL expression without diminution of osteoprotegerin expression.…”
Section: Discussioncontrasting
confidence: 83%
“…As noted above, A 2b promotes a phenotypical switch from M1 to M2 macrophages, 75-77 but also stimulates the differentiation of dendritic cells, which can promote type 17 T helper cells (T H 17) immune responses via production of IL-6 87-89 . Indeed, in in vivo studies high concentrations of adenosine exacerbated arthritis and tissue destruction in rats via an A 2b mechanism 90 .…”
Section: Adenosine Receptors and Innate Immunitymentioning
confidence: 99%
“…For example, while some have found the application of an A2BR-specific agonist, BAY60-6583 in murine bone marrow macrophages inhibits RANKL-induced osteoclast formation in a dose-dependent manner [53], this contrasts with the findings of Termachi et al who reported that adenosine blocked the MTX-induced osteoclast inhibition via A2BR activation [63]. These effects may be secondary to involvement of the A2BR receptor on osteoblasts, which play a crucial role in stimulating osteoclast differentiation via RANKL.…”
Section: P1 Receptors: A2br and A3rmentioning
confidence: 88%